Peningkatan Kinerja Pegawai Melalui Knowledge Sharing, Pelatihan dan Kompetensi - Ni Luh Putu Eka Yudi Pratiwi (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2021)
The results of this study stated that the parameter coefficient value of the effect of Knowledge Sharing on Employee Performance was positive and significant where the coefficient value was 0.542 and t value was 6.568 which turned out to be greater than t table 1.96 with a significant level of 0.000 <0.50 , the relationship between Training on Employee Performance is positive and significant where the coefficient value is 0.302 and t value is 3.400 with a significant level of 0.001 <0.50, the effect of Competency on Employee Performance is positive and significant where the coefficient value is 0.160 and the value of t is 2.499 which turns out to be greater than t table 1.96 with a significant level of 0.013 <0.50. So it can be concluded that the value of the positive coefficient and the value of t is greater than t table then it can be stated that the results of this study are significant so the first to third hypothesis is accepted.